Awareness and Practices for Dengue Prevention: A Cross -sectional study in the Sarojini Nagar Block of Lucknow, Uttar Pradesh, India - Monika Aggarwal; Rizwana Bano; Arunima Saini (Global Journal of Medicine and Public Health, 2025)
Dengue fever, caused by the Aedes aegypti mosquito, is one of the fastest-growing viral infections globally, posing a significant public health threat in over 100 countries. According to the World Health Organization (WHO), an estimated 390 million Dengue infections occur annually, with approximately 96 million manifesting clinically severe illness. 1 Objective 1. To assess the Knowledge about Dengue fever and its preventive measures among community members. 2. To identify behavioral practices and community attitudes that contribute to the rising cases of Dengue fever Methods A cross-sectional study was conducted in Sarojini Nagar Block situated in District Lucknow of State Uttar Pradesh, India, from July 2024 to September 2024.The dengue-related knowledge, attitudes and behaviours of a household, which was evaluated using a composite score divided into three categories: poor, satisfactory, and good. Twelve questions about dengue were provided to the participants in order to assess their level of knowledge; correct answers received a score of 1, while incorrect answers received a score of 0. Twelve(12) was the highest possible score.Data was analysed using SPSS 24 version. Result Awareness regarding mode of dengue transmission and breeding place of vector was high among participants but only 20.6% of participants correctly identified a virus as the cause of Dengue, while 57.3% did not know the cause, and 13.2% mistakenly thought it was caused by bacteria. Overall 37% of the participants had a satisfactory level of knowledge. Discussion Significant lack of understanding about the viral origin of Dengue presents a major public health concern. Awareness campaigns must focus on educating the public about the true cause of Dengue, as proper knowledge can enhance community engagement in vector control and reduce the spread of misinformation.